Küreselleşmenin Muhasebe Uygulamalarına Etkisi - (:unkn) unknown (My University, 2006)
Destek hizmeti veren muhasebe iktisadi gelişmelere uyum sağlayarak kendini yenilemektedir. Bilançonun, gelir tablosunun gelişmesi böyle olmuştur. Tek yanlı kayıt yönteminden çift yanlı kayıt yöntemine geçiş böyle olmuştur. Küreselleşme, muhasebenin XX. yüzyılın ikinci yarısında karşılaştığı bir konu olmuştur. Sosyalist blok ülkeleri muhasebenin uyumlaştırılması çalışmaları yapmışlardır. Batı ülkeleri de muhasebe uygulamalarının tekdüzenliğe kavuşturulması çalışmalarını Dünya Muhasebeciler Kongrelerinde yürütmüşlerdir. Uluslararası ilk uyumlaştırma, Avrupa Ekonomik Topluluğu'nda gerçekleşmiştir. Sosyalist düzenin çökmesinden sonra ise Uluslararası Muhasebe Standartları çerçeve¬sinde küreselleşme başlamıştır.

Accounting-a service of support-renews itself in accordance with the new developments in economics. The development of balance sheet and income table was as same as this situation. In addition, the use of double entry accounting system instead of single entry system realized through the same process. Accounting faced with the reality of globalization in the second half of 20th century. The states of socialist bloc did also work on the harmonization of accounting standards. The western countries maintained the harmonization studies within context of World Congresses of Accountants. The first international movement of harmonization occurred in the European Economic Community. After the collapse of socialist order, the pull of globalization motivated the work on international accounting standards.
The Impact of Globalization on Accounting Applications
Keywords: İktisat